Inkulturasi Iman Kristen dalam Konteks Budaya Batak: Suatu Tinjauan Misiologis - Raja Oloan Tumanggor (Cipanas Theological Seminary, 2021)
AbstractThe encounter between Christian faith and Batak culture is an important issue in mission activities. This encounter certainly faces various problems and tensions that can only be overcome by communication between cultures. This article seeks to map the experience of encounter Christian faith with Batak culture and religion. The inculturation of the Christian faith that was carried out at the beginning of the Catholic mission activities in the Batak lands was how to introduce the concept of a Christian God to the Batak people who actually have their own concept of God in their traditional religion. The process of inculturation requires the transformation of traditional Toba Batak culture through Christianity. Likewise, the transformation of Christianity through traditional culture. That is, there must be a reciprocal relationship between the Christian tradition and concrete culture in the sense of critical correlation. Reciprocal relationships will certainly bring tension. This process of inculturation is permanent and the gospel is expressed in a cultural context. The gospel is not only expressed with cultural elements, but also becomes a force capable of changing the life patterns of the Toba Batak people.Key words: inculturation, Christian faith, Toba-Batak. AbstrakPertemuan antara iman Kristen dan kebudayaan Batak merupakan isu penting dalam kegiatan misi. Pertemuan ini tentu menghadapi berbagai persoalan dan ketegangan yang hanya bisa diatasi dengan komunikasi antara budaya. Artikel ini berupaya memetakan pengalaman pertemuan iman Kristen dengan budaya dan religi Batak. Upaya inkulturasi iman Kristen yang dilakukan pada awal kegiatan misi Katolik di tanah Batak adalah bagaimana memperkenalkan konsep Allah kristiani kepada orang Batak yang sebenarnya juga telah memiliki konsep tersendiri mengenai Allah dalam agama tradisional mereka. Proses Inkulturasi membutuhkan transformasi budaya tradisional Batak Toba melalui kekristenan. Demikian juga sebaliknya transformasi kekristenan melalui budaya tradisional. Artinya, mesti ada suatu relasi timbal balik antara tradisi kekristenan dengan budaya konkrit dalam arti korelasi kritis. Relasi timbal balik tentu akan membawa ketegangan. Proses inkulturasi ini berlangsung permanen dan Injil diungkapkan dalam konteks budaya. Injil tidak hanya diungkapkan dengan elemen-elemen budaya, tapi juga menjadi kekuatan yang mampu mengubah pola kehidupan orang Batak Toba